(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Background: The Government of India launched SWAYAM, one of the largest Massive Open Online Courses platforms in the world, in 2016 with the primary goal of assisting in the provision of open-access online courses. The purpose of the current study was to assess the awareness and utilization of SWAYAM courses among health science teaching faculties. Material and Method: A cross-sectional questionnaire-based online survey was conducted among health science faculties. Frequency and percentage data were studied for online responses. Result: We observed that out of 311 participants, 126 (40.5%) were aware of SWAYAM massive open online platform, of which only 46(36.5%) had registered for SWAYAM massive open online courses. The most common reason for registration in the portal was to complete the mandatory basic research course and for getting certificate. Out of 46 participants enrolled in SWAYAM, 33(71.7%) could not complete their courses on SWAYAM platform, the most common reason for not completing being lack of time 18(55%).The commonest reason for non-enrollment (n = 185) observed was unawareness about courses on SWAYAM (51.4%) and preference to learn in classroom with others (15.8%). About the need of any awareness program regarding SWAYAM courses in their institute, most of them (84.9%) were willing for the same. Conclusion: Our survey revealed that SWAYAM this platform has its positive way of self-gaining knowledge, even at the grassroots level. Even though not many people are aware of the portal, mandates and requirements encourage people to self-enroll. Percolation of the concept of SWAYAM portal to individuals by the higher authorities is a must for proper utilization of the online MOOC platform.